Pendidikan Kesehatan Jiwa: Kupas Tuntas dan Skrining Gejala Borderline Personality Disorder - Endah Sarwendah; Tantan Hadiansyah; Triana Dewi Safaria; Nabilla Saktiana; Sarah Nurul Asyfa (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Borderline Personality Disorder or BPD is a personality disorder whose main symptoms include significant emotional changes, impulsive behavior, and impaired interpersonal and/or occupational functioning. Individuals diagnosed with BPD typically experience discrimination and stigma, resulting in poor identification and delayed treatment. The purpose of this community service is to provide mental health education and early detection of BPD in the community. The implementation method is carried out online via Zoom Meeting. Mental health education begins with pre- and post-tests to measure participants' knowledge before and after the education. There was a significant difference between the pre-test and post-test results for participants tested using the nonparametric Wilcoxon test (Asymp. Sig. (2-tailed) = 0.014). After that, participants were shown a display of the McLean Screening Instrument for early detection of BPD, along with its interpretation results. This is expected to prevent the emergence of stigma in individuals with BPD and help them recognize early symptoms of BPD, which are risk factors for suicide. In addition, participants can learn about their mental health condition and immediately seek help if needed.